Khumba [videorecording (DVD)] - Silverston, Anthony; Delle Donne, Raffaella; Austin, Jake T. (Jake Toranzo), 1994-; Buscemi, Steve, 1957-; Devine, Loretta; Fishburne, Laurence, III, 1961-; Grant, Richard E., 1957-; Robb, AnnaSophia, 1993-; Tate, Catherine; Neeson, Liam ([publisher not identified], 2014)
A half-striped zebra blamed for the drought in Great Karoo embarks on a quest to earn his stripes by finding the legendary waterhole and saving the animals back home.